Contamination of Tea and Coffee by Ochratoxin A in Hilla City, Iraq - Mohammad J Al-Jassani (Journal of Global Pharma Technology, 2018)
Analysis of several ground coffee and black tea samples sold in Hilla city market for Ochratoxin A (OTA) contamination. Ten of the most common Black tea and 10 Coffee samples were collected from the local ‎market. OTA was extracted following a standard technique then subjected to TLC analysis. All tested tea samples were found contaminated with OTA (100%). Five (50%) of coffee samples were found contaminated with OTA. This might indicate of bad quality tea have been ‎imported and/or with bad processing and packaging.‎ Iraq as a big importer and consumer of black tea is appeared ‎subjected to a high danger of OTA contamination. A very urgent concern need to be ‎directed and OTA safety level determination using HPLC for both imported and consumed tea ‎and coffee before marketing.Keywords: Coffee, Tea, Ochratoxin A, TLC.